Stochastic burstiness boundary analysis of LFSN-based self-similar network traffic model - YU Li; BAI Yun; ZHU Guang-xi (Tongxin xuebao)
A stochastic burstiness boundary of general LFSN（linear fractional stable noise）-based traffic model,which is an important model that has been proven capable to capture both properties of self-similar and heavy tailed,was derived.The final result is much more general than the current one,especially for the upper boundary which is also more accurate.Meanwhile,a unique experiment based on fast simulation of general LFSN process was set up to get an estimation result for actual distribution,which in turn proved theoretical derivation correct.